Effect of Dextrans in Vitro on the Adenosine Diphosphate Induced Adhesiveness of Human Blood Platelets - Bygdeman, S; Eliasson, R (Thrombosis and Haemostasis, 1966)
The effect of adding dextrans with Mw from 40,000 to 153,000 to blood samples on the ADP induced platelet adhesiveness to glass has been studied. It was observed that a dextran concentration in the plasma of 1 % did not change the adhesiveness, while a concentration of 1.5 and 2% caused a slight increase. The results make it less likely that the decreased tendency of the platelets to aggregate in vivo after dextran treatment, as described by other authors, is due to an effect on the ADP reactive receptors located on the surface of the platelets.